(3GdeNJUQ GdfGaYs - (3GdgPdj, GdMdj, CHh GdbGSe, fLe GdOjf, GdeMbb GdMdj, LYaQ Hf GdMSf Hf jMji Hf GdMSjf, J(B676(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg GdPj UZQJ aj YXeJg YHGOI GdYGHOjf CeG HYO aEfj ehQO aj gPG GdeNJUQ NdGUI GdePgH GdeYJHQ HCdaGX eMjQI hYHGQI eMQQIs
(3BNQgG (B:s
(3dG jYbd GdfGbI hdG GJdGa eGd hjNJU VeGfgG HGdLfGjI Ydi GdBOej MSH agPG eG ChQOfG PcQg hbUOfG MUQg eNJUQ eMUdgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2 / 123s
(3eYLe GdeDdajf (B1 / 490s
(3GdPQjYI (B2 / 186s
(3GdJQGK GdYQHj aj NRGfI eNWhWGJ GdeQYTj (B5 / 95s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3abg GdePGgH GdCNQis